Impact of motiation on employee performance - Mukamutesi Kellen (My University, 2024)
The study aimed at examining the impact of motivation on employee performance at KCCA. Objectives that guided the study included; the relationship between monetary rewards and employee performance, the relationship between recognition and employee performance and the relationship between motivation and employee performance. The findings showed that motivation had a profound impact on employee performance. The study shows that employees who receive monetary rewards work and achieve their performance targets, promotion opportunities lead to increased job satisfaction and that recognition strategies significantly impact employee performance. The limitation of the study was that it only focused on the impact of motivation on employee performance without considering other factors that may influence performance. The recommendations of the study were; to improve motivation and employee performance, KCCA should develop and implement effective motivation strategies such as recognizing and rewarding employees for their contributions.
Keywords: Motivation and Employees performance